Probability Analysis of Slope Failure at Pit C2H Blok B East Sambarata Mining Operation PT Berau Coal - ANGGARA (NIM : 12113077), HERU
Probabilistic method is an alternative approach in determining the stability of a slope, which can answer the possibility of a slope will experience lumps other than the value of safety factor (SF). The interesting thing about the probabilistic method is the explicit representation of the uncertainty in each parameter used in the analysis of the stability of the slope. In the end, the SF value can be optimized with the value of Probability of Failure (PF) so as to give a degree of confidence to the design. Slope analysis is done by limit equilibrium method using Slide program. The Point Estimate Method and Monte Carlo Method are used to analyze the probability of slope failure. Analysis has been done on 3 section of highwall slope. The result of analysis shows that by using the Point Estimate Method and Monte Carlo Method obtained Section with the largest probability of slope in section C. In the Point Estimate method, the acceptable slope angle for the 200 m slope height is 20 ° and 25 °, the higher the slope used, requires a more shallow angle to produce the appropriate PF value of the criterion. In the Monte Carlo method, the acceptable slope angle for 200 m slope height is 20 °, 25 °, and 30 °. For 250 m slopes are 20 °, 25 ° and 30 °. For a height of 300 m slope is 20 °. Value of Safety Factor when Probability of Failure 10% is obtained at 1.443. The Safety Factor of 1.4 applied as PT Berau Coal's minimum value for slopes of> 150 m high is not sufficient for slope design to be stable or safe, since the minimum SF value allowed when PF is 10% greater than 1.4 is 1.443